Long-term Effect of Organic Manures and Biofertilizers on Physical and Chemical Properties of Soil and Productivity of Rice-Wheat System - Kumar, Dhiraj; Purakayastha, T. J.; Shivay, Y. S. (International Journal of Bio-resource and Stress Management, 2015)
A field experiment was conducted at the research farm of Indian Agricultural Research Institute, New Delhi on a sandy clay-loam soil (Typic Ustochrept) starting from Kharif-2003 under organic amendments to rice-wheat cropping system. The experiment was laid out in a randomized block design with three replications and six treatments in a set. The treatments consisted of control (T1), farmyard manure (FYM) (T2); green manure (GM) (T3); GM+biofertilizers (B) (T4); GM+FYM (T5); and GM+FYM+B (T6). In this study, the effect of organic amendments were evaluated on some physical soil properties and yield of the respective system by sampling the soil from three depths (0-15, 15-30 and 30-60 cm) at the end of Rabi 2011-2012. The results of the study revealed that the plots where, farm yard manure (FYM) was incorporated along with green manure (GM) and biofertilizer (B), the yield of rice and wheat had substantially improved. The combination of B with GM+FYM had not only led to better soil bulk density but even prove superior to FYM alone or GM alone. Soil aggregation was significantly affected by organic amendments; particularly mean weight diameter (MWD) and geometric mean diameter (GMD) were increased to a tune of 73.5% and 34.6% over control in 0-15 cm soil layer. The water stable macroaggregate (WSMA)>0.25mm ranged from 54.60% under control to 71.27% under T6 in the surface soil (0-15 cm). The combined applications of FYM along with GM and B showed the highest contents of available N, P, K and S in soil. It is thus certain that the cumulative effect of GM+FYM+B proved to be the one that leads to increased productivity as well as increased soil physical properties.